Application of ultrasound renal doppler to detect changes in renal haemodynamics in patients with comorbidity of chronic obstructive pulmonary disease and essential hypertensio - Akimova, L.; Акімова, Лілія Сергіївна (My University, 2025)
The aim of the study. Assessment of changes in renal blood flow at the level of the common trunk of the renal artery (CTRA), segmental branches of the renal artery (SRA) and interlobular branches of the renal artery (ILRA) in the comorbid presentation of essential hypertension (EH) stage II with chronic obstructive pulmonary disease (COPD) of stages II-III.